Conception de référentiels et pédagogie de l’alternance des formations d’ingénieur - Stéphane Balas; Priscillia Riem (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper analyses the link between qualification frameworks for engineering diplomas and workplace learning. Both these strategies aim the same thing, i.e. professional development. Based on a questionnaire sent to engineering schools and interviews with key players in the reflections on professional development, we demonstrate that there are little connections between producing qualification frameworks responding to the national directives and the efficiency of workplace learning. We argue that links could be made in order to produce qualification frameworks aligned on the realities of work and a truly integrative workplace learning model.